A Comprehensive Survey on Mobility Management in 5G Heterogeneous Networks: Architectures, Challenges and Solutions - Gures, Emre; Shayea, Ibraheem; Alhammadi, Abdulraqeb; Ergen, Mustafa; Mohamad, Hafizal (IEEE-Inst Electrical Electronics Engineers Inc, 2024)
Indexed by Scopus